SELECTION OF DEFUZZIFICATION METHOD TO OBTAIN CRISP VALUES FOR REPRESENTING UNCERTAIN DATA IN A MODIFIED SWEEP ALGORITHM - Gunadi W Nurcahyo (Teknik Elektro Politeknik Negeri Padang, 2013)
A study of using fuzzy-based parameters for solving public bus routing problem with uncertain demand is presented. The fuzzy-based parameters are designed to provide data required by the route selection procedure. The uncertain data are represented as linguistic values which are fully dependent on the user’s preference. Fuzzy inference rules are assigned to relate the fuzzy parameters to the crisp values which are concerned in the route selection process. This paper focuses on the selection of the Defuzzification method to discover the most appropriate method for obtaining crisp values which represent uncertain data. We also present a step by step evaluation showing that the fuzzy-based parameters are capable to represent uncertain data replacing the use of exact data which common route selection algorithms usually use.